FAKTOR YANG MEMPENGARUHI TINGKAT KESEJAHTERAAN PETANI PADI SAWAH DI NAGARI TIKU SELATAN KECAMATAN TANJUNG MUTIARA KABUPATEN AGAM - Anisa, Prima Sari; Erita, Yeni; Zahara, Leni (STKIP PGRI Sumbar, 2013)
This study aims to determine the factors that affect the welfare of rice farmers in South Tiku Nagari Tanjung Mutiara Agam District. The study was descriptive correlational. The population in this study are all people who live in South Tiku Nagari Tanjung Mutiara Agam District, who are farmers, amounting to 372 farmers. Samples were taken with a proportional random sampling technique with the proportion of 20% that the sample amounted to 75 rice farmers. The research found that : 1 ) There is positive influence between the management of rice fields with the welfare of rice farmers in South Tiku Nagari Tanjung Mutiara Agam District because t calculate > t table ( 5.828 > 1.665 ) , the strength of the relationship categories is medium ( r = 0.564 ) with including small contribution is 31.8 % , 2 ) There is a positive influence between production rate with the welfare of rice farmers in South Tiku Nagari Tanjung Mutiara Agam District because tcalculate > t table ( 2.067 > 1.665 ) , low- power relationship ( r = 0.235 ) and the contribution of very small production rate that is equal to 5.5 % , 3 ) There is a marketing influence with the welfare of rice farmers in South Tiku Nagari Tanjung Mutiara Agam District because t calculate> t table ( 2.142 > 1.665 ) , the strength of the relationship is low ( r = 0.243 ) and a veryÂ small amount of the contribution is 5.9 % and 4 ) There is a positive influence between land management , the level of production and marketing together with the welfare of rice farmers in South Tiku Nagari Tanjung Mutiara Agam district because Fcalculate > F table ( 16.134 > 3.150 ) , the strength of the relationship is medium ( r = 0.637 ) and contributions , including quite large ( 40.5 % )